2017
DOI: 10.1055/s-0043-112246
|View full text |Cite
|
Sign up to set email alerts
|

Variability in, and factors associated with, sizing of polyps by endoscopists at a large community practice

Abstract: Background and aims  Accurate sizing of polyps at time of colonoscopy is critical for determining surveillance intervals. Endoscopists routinely over- or underestimate the size of polyps at colonoscopy. We evaluated the variability in sizing of polyps among multiple endoscopists, and the effect of patient and physician related factors on polyp size estimation in a large community-based practice. Methods  Adult patients who underwent a colonoscopy with polypectomy at five endoscopy centers in Minneapolis/St. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…However, the multivariable logistic regression analysis showed that factors significantly associated with a high improvement (≥10%) of accuracy after the educational video lecture included a lower score in the pretest as well as the category of beginners. Some studies showed interphysician variability in experts for the estimation of polyp size 13,21. Although we initially assumed beginners as a group with a low score in the pretest, experienced endoscopists can also make inaccurate measurements when estimating polyp size.…”
Section: Discussionmentioning
confidence: 99%
“…However, the multivariable logistic regression analysis showed that factors significantly associated with a high improvement (≥10%) of accuracy after the educational video lecture included a lower score in the pretest as well as the category of beginners. Some studies showed interphysician variability in experts for the estimation of polyp size 13,21. Although we initially assumed beginners as a group with a low score in the pretest, experienced endoscopists can also make inaccurate measurements when estimating polyp size.…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance interval recommendations depend strongly on polyp size, but measurement bias is present with evaluation both at endoscopy [34] and pathology [35]. It is known that at endoscopy size estimation is usually biased towards specific numbers (i. e., 5 or 10) while neglecting the others [34 -36], and interobserver variability in visual polyp sizing can be present [37,38], resulting in routine underestimation or overestimation of polyp size [39,40]. However, such bias can be reduced by using a reference standard, such as an open biopsy forceps or snare [41 -43].…”
Section: Polyp Size Evaluationmentioning
confidence: 99%
“…While not replicated in humans, they estimated distance with a mean error of <0.01 cm over 20 cm of travel 21 . Size estimation was less accurate with a mean absolute error of approximately 20%, although this compares favorably to expert endoscopist visual estimates 21,47 …”
Section: Measurement and Capsule Localizationmentioning
confidence: 91%